Short-Chain Fatty Acids: A Soldier Fighting Against Inflammation and Protecting From Tumorigenesis in People With Diabetes - Yang, Qiyu; Ouyang, Jing; Sun, Fengjun; Yang, Jiadan (Frontiers in Immunology, 2020)
Converging evidences showed that people with diabetes mellitus (DM) have significantly higher risk for different cancers, of which the exact mechanism underlying the association has not been fully realized. Short-chain fatty acids (SCFAs), the fermentation products of the intestinal microbiota, are an essential source for energy supply in gut epithelial cells. They have been reported to improve intestinal barrier integrity, prevent microbial translocation, and further dampen inflammation. Gut dysbiosis and reduction in SCFA-producing bacteria as well as SCFAs production in the intestine are commonly seen in metabolic disorders including DM and obesity. Moreover, inflammation can contribute to tumor initiation and progression through multiple pathways, such as enhancing DNA damage, accumulating mutations in tumor suppressor genes Tp53, and activating nuclear factor-kappa B (NF-κB) signaling pathways. Based on these facts, we hypothesize that lower levels of microbial SCFAs resulted from gut dysbiosis in diabetic individuals, enhance microbial translocation and increase the inflammatory responses, inducing tumorigenesis ulteriorly. To this end, we will discuss protective properties of microbial SCFAs, and explore the pivotal roles SCFAs played in the link of DM with cancer, so as to take early precautions to reduce the risk of cancer in patients with DM.